MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN MELALUI MODEL PEMBELAJARAN KOOPRATIF TIPE NHT KELAS IIB SDN KEBONAGUNG 2 SUKODONO - Nur Kholifatul Ula; Andi Wapa (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
The low learning outcomes of class IIB students at SDN Kebonagung 2 Sukodono in adding material in mathematics lessons became the trigger for this research. This is due to the lack of effectiveness of teachers in the learning process in using learning methods. Students who are still confused and find it difficult to imagine what is being learned because they have not mastered the additional material properly and correctly. so that the motivation of students in participating in mathematics learning material is still not optimal. From the explanation of this problem, the purpose of this exam is to further develop material for additional mathematics learning outcomes by applying the cooperative learning model for NHT class IIB students at SDN Kebonagung 2 Sukodono. Two cycles of classroom action research were used in this improvement strategy. Each cycle comprises of four phases including: preparing, carrying out, observing, and contemplating (reflection). Discussion and analysis of data 89 Jurnal FKIP – Universitas Bakti Indonesia Vol 2 No 2 (2023) Meningkatkan Hasil Belajar Matematika Materi Perkalian Melalui Model Pembelajaran Koopratif Tipe Nht Kelas IIB SDN KEBONAGUNG 2 SUKODONO regarding the application of the NHT cooperative learning model can improve student learning outcomes, especially in pre-cycle 74.50, cycle I 80.83, and cycle II 89.00.